The Epilepsy Risk Awareness (ERA) Scale: A New Era for Holistic Risk Assessment in Epilepsy - Ison, Rachel; Kisan, Virad; Cole, Christine; Angus-Leppan, Heather (Frontiers in Neurology, 2020)
Objective: Best care in epilepsy balances protecting people with epilepsy from risks and avoiding undue restrictions in order to improve quality of life. To date, no single risk assessment tool has been widely adopted by both people with epilepsy and health care professionals such as specialist epilepsy nurses. The present research refined the Epilepsy Risk Awareness (ERA) Scale, a validated and holistic risk assessment tool, by assessing test-retest reliability of each question and incorporating suggestions from patients regarding design and content. Methods: The draft clinical Scale was administered to 102 adult participants from the Epilepsy Service at the Royal Free London NHS Foundation Trust on two occasions. Quantitative and qualitative analyses were conducted – intra-class correlation coefficient (ICC) estimates were used to assess test-retest reliability of questions, and Thematic Analysis was used to analyse participants’ comments and feedback. Following analysis, the ERA Scale was amended. Of the 102 participants, 32 conducted a further review of the revised ERA Scale to test completion time and provide final comments. Results: ICC reliability level estimates varied from ‘poor to moderate’ to ‘good to excellent’, and four qualitative themes were identified. The ERA Scale was amended accordingly to enhance practicality and usefulness, reducing completion time to approximately 5 minutes. Significance: The ERA Scale is a validated tool that aims to change clinical practice by standardising risk assessment in epilepsy, providing a holistic approach that focuses on improved safety and quality of life.